Firm-Level Productivity Spillovers from FDI in Latin American Countries - Henning Mühlen (Ruhr-Universität Bochum, Institut für Entwicklungsforschung und Entwicklungspolitik (IEE), 2013)
Foreign direct investment (FDI) projects are assumed to be accompanied by potential external effects - so-called FDI spillovers - which are supposed to affect productivity levels of other firms in a host country. Empirical results on this topic are inconclusive and most studies focus on one country. I contribute to the literature by employing comparable firm-level panel data from ten Latin American (developing) countries in order to estimate the spillover effects from FDI on firms' productivity levels. The impact is assessed as an average effect for the full set of countries as well as for each economy separately. The results indicate that there is a small negative spillover effect from foreign presence within industries across Latin American countries. Furthermore, I find that the negative intra-industry spillover is caused by wholly owned foreign affiliates. The country-specific investigation indicates that the spillover effects differ between the considered economies with a tendency that the presence of FDI in a sector (region) has a negative (positive) impact.
Keywords: F21; F23; O33; 330; Foreign direct investments; Spillovers; Firm-level panel data; Enterprise surveys; Latin America; Developing countries; Auslandsinvestition; Ausländisch; Produktivität; Spillover-Effekt; Lateinamerika; Entwicklungsländer